Redevelopment of undergraduate food microbiology capstone projects for unprecedented emergency remote teaching during the COVID-19 pandemic: then and now - Chaminda Senaka Ranadheera; Yianna Zhang (Microbiology Australia, 2023)
Unprecedented emergency remote teaching (ERT) during the COVID-19 lockdowns has hindered research-based learning in the life sciences worldwide, holding potential consequences for the students’ ability to develop essential skills for the contemporary workforce. In this article, we report redevelopment of an undergraduate capstone subject in the food science major at The University of Melbourne for bichronous ERT delivery, which previously aimed to provide students with analytical, problem-solving and communication skills through laboratory-based practical experimentation or internship projects. When in-person exchanges became unfeasible during 2020, we redesigned the online learning environment to best facilitate personalised learning and collaborative relationships between learners, instructors and subject content. This includes the redevelopment of laboratory-based projects as data mining or literature reviews delivered under four major themes including food microbiology. Despite the drawbacks in peer-based interactions through remote delivery, participation in design-based research remains a viable approach to support students in gaining essential transferrable skills during ERT.